Возможности повышения эффективности малых паротурбинных ТЭЦ за счет их расширения газотурбинными надстройками - Шубенко, А. Л.; Лыхвар, Н. В.; Синецкий, А. В. (НТУ "ХПИ", 2010)
Possibility of increase of efficiency of steam-turbines HEC of industrial factories due to their expansion by gas-turbines buildings is examined. Estimation of expedience of add of exhausting gases of GTU in a power steam-boiler with the use of additional incineration of fuel. Researches are conducted with the bundled software developed in IPMash NANU. Bundled software allows to conduct calculations not only depending on the type of fuel, but also from his composition. This bundled software takes into account great number of external and internal influencing factors. The results of calculations showing changes the indexes of SGU at presence of additional incineration of fuel in PSB.
Keywords: теплоэнергетика; стоимость энергии; режимы энергоустановок; ПГУ